Work-From-Home During COVID-19 Lockdown: When Employees’ Well-Being and Creativity Depend on Their Psychological Profiles - Michinov, Estelle; Ruiller, Caroline; Chedotel, Frédérique; Dodeler, Virginie; Michinov, Nicolas (Frontiers in Psychology, 2022)
With the COVID-19 pandemic, governments implemented successive lockdowns that forced employees to work from home (WFH) to contain the spread of the coronavirus. This crisis raises the question of the effects of mandatory work from home on employees’ well-being and performance, and whether these effects are the same for all employees. In the present study, we examined whether working at home may be related to intensity, familiarity with WFH, employees’ well-being (loneliness at work, stress, job satisfaction, and work engagement) and creativity (‘subjective’ and ‘objective’). We also examined whether the psychological profile of employees, combining preference for solitude and associated personality variables from the Big Five, may influence the effects of WFH. The data were collected via an online survey from November 13th to December 15th 2020 among 946 employees from various organizations during the second lockdown in France. In addition to identifying two distinctive psychological profiles for employees having to WFH, results revealed that those with a “Solitary” profile reported higher loneliness at work, higher levels of stress, and lower levels of job satisfaction and work engagement than those with an “Affiliative” profile. It was also found that employees with a “Solitary” profile perceived themselves as less creative and produced objectively fewer ideas than individuals with an “Affiliative” profile. The present study suggests the necessity to distinguish the profiles of teleworkers and to offer a stronger support for the less affiliative employees when working from home.